4(g+7)+8=2g-8

Simple and best practice solution for 4(g+7)+8=2g-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(g+7)+8=2g-8 equation:


Simplifying
4(g + 7) + 8 = 2g + -8

Reorder the terms:
4(7 + g) + 8 = 2g + -8
(7 * 4 + g * 4) + 8 = 2g + -8
(28 + 4g) + 8 = 2g + -8

Reorder the terms:
28 + 8 + 4g = 2g + -8

Combine like terms: 28 + 8 = 36
36 + 4g = 2g + -8

Reorder the terms:
36 + 4g = -8 + 2g

Solving
36 + 4g = -8 + 2g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-2g' to each side of the equation.
36 + 4g + -2g = -8 + 2g + -2g

Combine like terms: 4g + -2g = 2g
36 + 2g = -8 + 2g + -2g

Combine like terms: 2g + -2g = 0
36 + 2g = -8 + 0
36 + 2g = -8

Add '-36' to each side of the equation.
36 + -36 + 2g = -8 + -36

Combine like terms: 36 + -36 = 0
0 + 2g = -8 + -36
2g = -8 + -36

Combine like terms: -8 + -36 = -44
2g = -44

Divide each side by '2'.
g = -22

Simplifying
g = -22

See similar equations:

| |x-11|=15 | | 10x-147+x=73 | | 8xsquared-140x+300=0 | | n+8.7=1.62 | | 7(x-3)+5=4(3x-2)-8 | | 12=4(X-8)+16 | | 6(x-4)-5(x-2)-7(2x+5)=3 | | 4x^2-20+6x=0 | | 7x-28-3=46 | | 2x+8x+2y^2=0 | | 3x=4-(-14) | | -12+6x-4x=18 | | x^2+y^2+2x+4y-20=0 | | 105x+15x-225=25 | | -4(6m+1)=-17m-18 | | 10x-5(2x+4)=20 | | 7(8v+1)=231 | | 4a-3b=10 | | 10x-x-134=118 | | 1.5x+3x-4=10 | | 15p+7p= | | 2x^2-5x-133=0 | | S=D+pm | | 3*3/10+4=-3 | | -2W+5-3W-4=-9 | | 3*-7/4+4=-3 | | 2.4(2x-2)+2.2x= | | .06x+.5=.123 | | X+45=600 | | (11b-6)-5(2b+4)=-6 | | 10(x+5)=12(x-4) | | 17p+14+19=3 |

Equations solver categories